2013
DOI: 10.1530/jme-13-0072
|View full text |Cite
|
Sign up to set email alerts
|

Molecular pathways involved in the improvement of non-alcoholic fatty liver disease

Abstract: Non-alcoholic fatty liver disease (NAFLD) and non-alcoholic steatohepatitis are components of the metabolic syndrome. Serum leptin levels are elevated in obesity, but the role of leptin in the pathophysiology of the liver involvement is still unclear. To identify the effects and mechanisms by which leptin influences the pathogenesis of NAFLD, we performed epididymal white adipose tissue (eWAT) transplantation from congenic wild-type mice into the subcutaneous dorsal area of Lep ob/ob recipient mice and compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…In another patient, it has also been shown that LRT reduces circulating levels of transaminases, total cholesterol, LDL, insulin resistance, and liver fat content (36). Similarly, our previous research has shown that white adipose tissue transplantation from wild-type mice into genetically obese and leptin deficient ob/ob mice leads to the improvement of several metabolic parameters, and to the reversal of nonalcoholic fatty liver disease, due to the correction of the leptin-deficient state (37).…”
Section: Discussionmentioning
confidence: 79%
“…In another patient, it has also been shown that LRT reduces circulating levels of transaminases, total cholesterol, LDL, insulin resistance, and liver fat content (36). Similarly, our previous research has shown that white adipose tissue transplantation from wild-type mice into genetically obese and leptin deficient ob/ob mice leads to the improvement of several metabolic parameters, and to the reversal of nonalcoholic fatty liver disease, due to the correction of the leptin-deficient state (37).…”
Section: Discussionmentioning
confidence: 79%
“…Thus, the pattern of adaptation in the MMA hepatocyte is characterized by increased expression of genes involved in the disposal of "toxic" metabolites, cell survival, liver regeneration, and an oxidant stress response, with an accompanying transcriptional signature of metabolic rechanneling of lipid and glucose metabolism. Because similar pathways are implicated in the etiology of nonalcoholic fatty liver disease and steatohepatitis (52)(53)(54), conditions which MMA patients may be prone to develop (47), these differentially regulated genes, as a group, may harbor fruitful targets for small-molecule modulation.…”
Section: Discussionmentioning
confidence: 99%
“…SubQ→Vis transplantation likely prevents HFD-induced glucose intolerance and IR by altering the balance of these cell types specifically in the intra-abdominal compartment, as SubQ→SubQ transplantation does not affect glucose tolerance [19,20]. While further studies will be required to fully understand how this procedure affects immune cell populations, it will be important to consider migration of cells from donor AT to other tissues, including liver and spleen, following transplantation [41]. We were unable to relate differences in plasma cytokine concentrations to mRNA expression in grafted or endogenous AT (Fig.…”
Section: Discussionmentioning
confidence: 99%